2005
DOI: 10.1074/jbc.m410604200
|View full text |Cite
|
Sign up to set email alerts
|

SOCS-3 Induces Myoblast Differentiation

Abstract: Myoblast differentiation is characterized by a sequence of events that includes an increase in insulinlike growth factor (IGF)-I and contractile gene expression. The increase in IGF-I expression activates cell signaling mechanisms that participate in the differentiation process. One potential contributor is the SOCS-3 (suppressor of cytokine signaling-3) gene, which regulates signaling mechanisms and may be sensitive to changes in IGF-I concentrations. For the first time, the role of SOCS-3 is investigated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1
4

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 58 publications
3
40
1
4
Order By: Relevance
“…SOCS-3 is induced in response to IGF1 in neurons, and antagonises its effect on survival through binding to the IGFR1 (Yadav et al 2005). IGF1 also upregulates SOCS-3 during differentiation of myoblasts, thus inducing transcriptional activation of the a-actin promoter (Spangenburg 2005).…”
Section: Socs-3 Is a Regulator Of Receptor Tyrosine Kinasesmentioning
confidence: 99%
“…SOCS-3 is induced in response to IGF1 in neurons, and antagonises its effect on survival through binding to the IGFR1 (Yadav et al 2005). IGF1 also upregulates SOCS-3 during differentiation of myoblasts, thus inducing transcriptional activation of the a-actin promoter (Spangenburg 2005).…”
Section: Socs-3 Is a Regulator Of Receptor Tyrosine Kinasesmentioning
confidence: 99%
“…It was recognized several years ago that SOCS2 could interact with and inhibit the IGF-1R [52]. It has been subsequently demonstrated that not only could IGF-1R be affected by SOCS proteins, but that IGF-1R signaling could upregulate the expression of SOCS3 directly [53]. Stem cell factor (SCF) receptor (kit) is another receptor tyrosine kinase that is relevant to hematopoietic recovery since it is expressed on a variety of stem cells.…”
Section: Socs Effects On Receptor Tyrosine Kinasesmentioning
confidence: 99%
“…Furthermore, SOCS-3 has been identified as a regulator of myoblast differentiation. 18 To understand better the mechanisms of IL-6/JAK/ STAT3 signaling in benign and malignant prostate tissue, we have assessed expression of SOCS-3 in prostate cells and in material obtained from patients. The mechanisms responsible for changes in SOCS-3 expression were investigated.…”
mentioning
confidence: 99%